Strategic predisposition in communication management: understanding organizational propensity towards bridging strategy. Issue 3 (1st August 2016) - Kim, Soojin
Abstract : Purpose: This study attempts to identify factors influencing an organization's predisposition to bridging strategy, and tests relationships between those factors and bridging strategy. Design/methodology/approach: Online survey was conducted in South Korea. Hierarchical regression was used. Findings: Identified factors are environmental complexity, top management attitude toward stakeholders, analysis orientation, and authoritarian culture. Research limitations/implications: By adopting the concept and measures of bridging as an organization's public-engagement strategy, this study was able to capture an organization's strategic approach for problem-solving in communication management. Practical implications: Strong analysis orientation allows organizations to look into problems in their complex environments affecting their performance and their key stakeholders before deciding on strategies; resultantly, they are more likely to reduce problems and to improve their performance. In contrast, authoritarian culture discourages an organization's adoption of bridging strategy. Originality/value: This study is the first empirical study investigating the dynamics of factors influencing organizations' strategic predisposition in communication management.